Strategi Kepala Sekolah dalam Meningkatkan Budaya Literasi di Sekolah UPT SMPN 35 Medan - Nasution, Salniati; Hasyim Basid; Abdul Fattah Nasution; Dara Avira (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
The development of the times demands an improvement in literacy skills as a complex and essential life skill for every individual. However, the literacy level in Indonesia is still relatively low, as indicated by the results of the 2019 PISA survey which placed Indonesia at 62nd out of 70 countries. Schools, as formal educational institutions, play a central role in fostering a culture of literacy, and school principals hold a key position in directing and implementing literacy strategies within the school environment. This study aims to examine the strategies of principals in enhancing the culture of reading and writing literacy at UPT SMPN 35 Medan. Based on initial observations, the habituation of a literacy culture in that school has not yet become a priority, as reflected in the still low results of the Minimum Competency Assessment (AKM). This research employs a qualitative approach with data collection techniques through documentation and interviews. The data is analyzed using The model by Miles, Huberman, and Saldana (2014) includes the stages of data collection, reduction, presentation, and conclusion drawing. The results of the study are expected to reveal the effectiveness of the principal's role in advancing the culture of literacy, as well as contribute to formulating more optimal literacy strategies in the school environment. Kata kunci: : Literacy Culture, School Principal, Reading and Writing Literacy, Leadership Strategies, UPT SMPN 35 Medan